2015
DOI: 10.1007/s12192-015-0608-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of a heat-shock protein 70 gene in Polycelis sp.

Abstract: Heat-shock protein 70 (HSP70) is ubiquitously found in a variety of organisms and plays an important role in cytoprotection, environmental monitoring, and disease resistance. In this study, the full-length complementary DNA (cDNA) of hsp70 from planarian Polycelis sp. was first cloned using rapid amplification of cDNA ends (RACE). The expression levels of Pyhsp70 were analyzed in the presence of various stressors by real-time PCR, and its temporal-spatial expression patterns were also examined in both intact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…In intact animals, the transcripts of Djhsp60and Djhsp70-related gene (Djmot) have been detected in parenchymal tissue, where the neoblasts are distributed, and these transcripts have been upregulated in the regenerative blastema (Conte et al 2009(Conte et al , 2010Fernandez-Taboada et al 2011;Isolani et al 2012;Cheng et al 2015). In our work, the expression level of Djhsp40 gradually increased during regeneration, and the transcripts were distributed specifically in the blastema, where neoblasts and their descendants migrated to regenerate the lost body parts.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In intact animals, the transcripts of Djhsp60and Djhsp70-related gene (Djmot) have been detected in parenchymal tissue, where the neoblasts are distributed, and these transcripts have been upregulated in the regenerative blastema (Conte et al 2009(Conte et al , 2010Fernandez-Taboada et al 2011;Isolani et al 2012;Cheng et al 2015). In our work, the expression level of Djhsp40 gradually increased during regeneration, and the transcripts were distributed specifically in the blastema, where neoblasts and their descendants migrated to regenerate the lost body parts.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies revealed that hsp70 and hsp60 genes are involved in planarian regeneration (Conte et al 2009(Conte et al , 2010Fernandez-Taboada et al 2011;Isolani et al 2012;Cheng et al 2015); therefore, we aimed to understand whether hsp40 gene is also involved in this process. We employed qPCR to detect the dynamic changes in Djhsp40 expression at different days following amputation.…”
Section: Expression Patterns Of Djhsp40 During Planarian Regenerationmentioning
confidence: 99%